Characterization of drug resistance and the defective HIV reservoir in virally suppressed vertically infected children in Mali. (19th February 2020) - Brice, Josephine; Sylla, Mariam; Desire, Nathalie; Sayon, Sophie; Telly, Fatoumata; Bocar-Fofana, Djeneba; Murphy, Robert; Peytavin, Gilles; Diallo, Souleymane; Nastouli, Eleni; Calvez, Vincent; Marcelin, Anne-Geneviève; et al.
Abstract: Background: In the perspective of ART-free HIV remission, vertically infected children treated with suppressive ART from early infancy represent an optimal population model to better understand the genetic complexity of the reservoir. Objectives: To evaluate the proportion of defective viral population and the genotypic resistance patterns in cell-associated HIV DNA. Methods: In a cohort including 93 ART-treated vertically HIV-infected (VHIV) children in Mali with plasma HIV-1 RNA ≤50 copies/mL for at least 6 months, we studied total HIV DNA, percentage of defective genomes and resistance by reverse transcriptase and protease bulk sequencing from whole blood in dried blood spots. Results: Children had a median age of 9.9 years at the time of inclusion (IQR = 7.6–13.4) and 3.3 years (IQR = 2–7) at ART initiation; median ART duration was 5.5 years (IQR = 3.7–7.3). The median level of total HIV DNA was 470 copies/10 6 cells with one patient presenting undetectable HIV DNA (<66 copies/10 6 cells). We observed the presence of at least one stop codon in viruses from 34 patients (37%). The presence of stop codons was not correlated with the level of HIV DNA or duration of ART. We showed a high prevalence of HIV-1 resistance in DNA with 26% of children harbouring virus resistant to at least one NRTI and 40% to at least one NNRTI. Conclusions: While these VHIV children were successfully treated for a long time, they showed high prevalence of resistance in HIV DNA and a moderate defective HIV reservoir.